2019
DOI: 10.22354/in.v23i3.789
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract infections and their Microbiological Spectrum- A study from coastal region of Southern India

Abstract: Objective: Biliary tract infections include cholangitis and cholecystitis. They are associated with high morbidity and mortality in elderly patients with co-morbid disease. The present study was undertaken to determine the microbial aetiology causing biliary tract infections and also to study their antimicrobial resistance profile.Materials & methods: A retrospective study was conducted from January 2011 to December 2016 at the Enteric Diseases Division, Kasturba Medical College Hospital, Manipal. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Among NAC, C. glabrata was recorded in both of their studies individually. Studies from Marak ( 25 ) and Ballal et al ( 26 ) revealed the presence of only NAC in bile which is in line with our study. In a study by Baghdadi et al 2016, C. albicans was the most common species isolated from endotracheal tubes accounting for 35.7%.…”
Section: Discussionsupporting
confidence: 93%
“…Among NAC, C. glabrata was recorded in both of their studies individually. Studies from Marak ( 25 ) and Ballal et al ( 26 ) revealed the presence of only NAC in bile which is in line with our study. In a study by Baghdadi et al 2016, C. albicans was the most common species isolated from endotracheal tubes accounting for 35.7%.…”
Section: Discussionsupporting
confidence: 93%
“…This is due to the careful setup in our microbiology laboratory, which led to better pathogen isolation without any delay due to transportation. Our results are consistent with other international studies that reported E. coli as the most common bacterial pathogen found in the bile of malignant biliary obstruction, diabetic patients, and after ERCP intervention 17–21 . Also, E. coli was found to have a strong association with ascending cholangitis, which leads to poor clinical outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with other international studies that reported E. coli as the most common bacterial pathogen found in the bile of malignant biliary obstruction, diabetic patients, and after ERCP intervention. 17 , 18 , 19 , 20 , 21 Also, E. coli was found to have a strong association with ascending cholangitis, which leads to poor clinical outcome. We carried out extensive search of published studies in the literature but could not find any specific findings describing poor clinical outcome or poor sepsis control of E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations